Journalism and Media Future - Creating Identity and Reality - Slađana Stamenković (In Medias Res, 2015)
Media and journalism are in constant uncertainty caused by the influence of online communities . A certain change is: ways of content distribution to consumers, media content and its production. Changes induced by metamedia - the internet is changing the position of the media market and the fundamental role of journalism. In response to these challenges in the U.S. several years ago began to develop the concept of "entrepreneurial journalism" that is still relatively unknown in the European public. Computers write news for, and artificial-intelligence experts at Google, predict that by of 2029. PCs to be smarter than the people, that in the next 15 years become more and more intelligent and will be able to understand what you 're talking about, learn from experience, they joke, tell stories, and even flirt. Journalism still has not found the outlines of his new identity, but it partly determines the logic of speed, brevity and superficiality of competition. The role of the editor is changing drastically - the editor should develop a vision angle and create an environment of different specialists who will thoughtfully implement it in practice. To have a greater effect on advertisers, journalists and editors are expected to not act in isolation in relation to the media business, and they know the mechanisms that determine whether and how advertisers appear within the online media. Respecting editorial integrity, journalists are the ones who should influence the greater engagement of readers. New professions in mediasfera is the creator of Content Curation, which are of great use journalistic and editorial experience. Computer - mediated communication replaces the actual communication and the media no longer represent reality but create it. In such circumstances, the media are no longer defined by their monopolistic or oligopolistic status, but their position in the market is determined to create their own identity in the online environment without boundaries. Classic media are still in the process of seeking effective business model and profit model that will replace the models that no longer work. In the next few years, creating content as the area will be the backbone of the formation of the Company's budget for the three dependent areas - media, marketing and PR. Ignoring the changes in media and journalism that the developed world is driven only means that some media will not survive, that some journalists will lose their jobs or become preparers content. Changes as a permanent modus vivendi in Serbia and the region are visible through a change in the way the media and the changing structure media content, which is the subject of the research conducted for this study. To predict the future of media and journalism are needed facts in the absence of which it is possible to rely on the thinking and experience of developed media community. One thing is certain: journalism and the media will not function the way it was before.